THE INFLUENCE OF DIGITAL FINANCIAL LITERACY ON THE PROFITABILITY OF MSMES IN KEMANG DISTRICT - Fadilah Rizki Andini; Aza El Munadiyan (Journal Informatic, Education and Management (JIEM), 2026)
Digital transformation according to Micro , Small and Medium Enterprises (MSMEs) to participate with financial technology to maintain business continuity . This study aims to analyze the effect of digital financial literacy on increasing the profitability of MSMEs in Kemang sub-district . The research approach used is quantitative with a causal associative design . Data were collected through a questionnaire with a Likert scale of 1-5 to 100 MSME respondents selected using a purposive sampling technique . Data analysis was carried out using simple linear regression through SPSS software . The results of the study indicate that digital financial literacy has a positive and significant influence on the profitability of MSMEs, with a calculated t value of 13.791> t table 1.984 and a significance value of 0.000 <0.05. The coefficient of determination (R2 ) shows that the digital financial literacy variable contributes 66 % to the variation in profitability , while the remaining 34% is influenced by other factors outside the research model . This finding confirms that mastery of financial technology can improve operational efficiency and accuracy of financial management which has a direct impact on increasing the net profit of MSME actors .